Pneumothorax in AIDS: case reviews and proposed clinical management. Issue 4 (August 1996) - Asboe, D; Fisher, M; Nelson, M R; Kaplan, D K; al-Kattan, K; Gazzard, B G
Abstract : BACKGROUND: Pneumothorax is a not uncommon complication of advanced HIV infection, and may prove difficult to manage in view of its recalcitrant and recurrent nature. In this group where immunosuppression and reduced life expectancy are a feature, standard protocols are often abandoned in favour of a more conservative approach. This is often unsuccessful. METHODS: Patients attending the Department of Genitourinary Medicine, Chelsea and Westminster Hospital who sustained pneumothorax between 1988 and 1992 were identified retrospectively and their notes reviewed. RESULTS: Fifteen patients were identified of whom three had post-procedural pneumothoraces. In the remaining 12 patients, 10 had previously had Pneumocystic carinii pneumonia (PCP), whilst all 12 had some evidence to suggest current PCP (seven proven, five presumptive). In those six patients with a single, unilateral pneumothorax, four were managed successfully with intercostal drainage alone (one patient died early, one required pleurectomy). In those with recurrent pneumothoraces or pneumothoraces that did not respond to prolonged intercostal drainage, failure of medical treatment was judged to have occurred and surgery was performed. Overall, conservative management failed in 7/11 patients. Conversely surgery resulted in resolution in 7/7 with recurrence seen in one individual. Median survival was similar in the two groups. CONCLUSIONS: Pneumothorax in patients with AIDS is associated with a high rate of intercurrent PCP; a low threshold for treating this infection presumptively is indicated. Intercostal drainage was successful in patients with a single, unilateral pneumothorax. However, in patients with recurrent or bilateral pneumothorax extended periods on intercostal drainage were uniformly unsuccessful. Early surgical referral should be considered in this group.